Similarity in mycorrhizal communities associating with two widespread terrestrial orchids decays with distance. (17th October 2019) - Xing, Xiaoke; Gao, Yue; Zhao, Zeyu; Waud, Michael; Duffy, Karl J.; Selosse, Marc‐André; Jakalski, Marcin; Liu, Na; Jacquemyn, Hans; Guo, Shunxing
Abstract: Aim: Interactions with mycorrhizal fungi are increasingly recognized as an important factor underlying the distribution and abundance of orchid species. However, the geographical distribution of orchid mycorrhizal fungi (OMF) and how their communities vary over large geographical areas are less well understood. Because climatic and environmental similarity may decrease with geographical distance or because some OMF have limited dispersal capabilities, similarities in orchid mycorrhizal communities can be expected to decrease with increasing distances separating orchid populations. However, up till now empirical evidence is largely lacking. Location: Eurasia. Taxa: Gymnadenia conopsea (L.) R. Brown and Epipactis helleborine (L.) Crantz. Methods: High‐throughput sequencing was used to perform a cross‐continental comparison of OMF that associate with two widespread Eurasian terrestrial orchids, Epipactis helleborine and Gymnadenia conopsea . Both phylogenetic and nonphylogenetic measures of community dissimilarity and their components were calculated and related to geographical distances using Mantel tests. Results: Our results showed that in both orchid species similarity in mycorrhizal communities decreased significantly with geographical distance. Decomposing the contribution of spatial turnover and nestedness to overall dissimilarity showed that the observed dissimilarity was mainly the result of species replacement between regions, and not of species loss. Similarly, a strong relationship was observed between phylogenetic community dissimilarity and geographical distance. Decomposing PCD values into a nonphylogenetic and phylogenetic component showed that orchid populations located closely next to each other were likely to contain the same operational taxonomic units (OTUs), but that the non‐shared taxa came from different phylogenetic clades. Species indicator analyses showed that the majority of OMF OTUs were restricted to particular geographical areas. However, some OTUs occurred in both continents, indicating that some fungi have very wide distributions. Main conclusions: Overall, these results demonstrate that orchid mycorrhizal communities differ substantially across large geographical areas, but that the distribution of orchids is not necessarily restricted by the distribution of particular OMF. Hence, widespread orchid species can be considered mycorrhizal generalists that are flexible in the OMF with which they associate across large geographical areas.